(untitled) (Homoeopathy for All, 2025)
Homeopathy was introduced in India in the early 19th century. It first flourished in Bengal and later spread throughout the country. In the beginning, the system was widely practised by amateurs in the civil and military services and others. Mahendra Lal Sircar was the first Indian who became a homeopathic physician, inspiring many allopathic doctors to follow his lead and begin homeopathic practice.The Calcutta Homeopathic Medical College, established in 1881, was the first homeopathic medical college in India and played a major role in popularising homeopathy across the nation.Homeopathy is a holistic system of medicine with a long history of use in health maintenance, disease prevention, and treatment, particularly for chronic diseases. In modern times, patients and health care providers alike are calling for health services that emphasize individualized, person-centred care. A wide variety of natural sources—plants, animals, minerals, nosodes, and sarcodes—serve as the basis for homeopathic medicines.